The image of concept «Kashyktyk» in space and time (Journal of Oriental Studies, 2016)
This article provides a definition of the concept. States that can be considered the concept of «Kashyktyk» as a concept. Defined image of the concept «Kashyktyk « in space and time. The image of the above-mentioned concept is revealed through the phrase and phraseological units.
Keywords: concept; language concepts; distance; space; time; language world; measure.